1981
DOI: 10.1152/jappl.1981.51.1.90
|View full text |Cite
|
Sign up to set email alerts
|

Control of release of surfactant phospholipids in the isolated perfused rat lung

Abstract: We used the isolated rat lung to investigate surfactant release. The lung was ventilated at 60.min-1 with 5% CO2-95% O2 and perfused at 10 ml.min-1 with Krebs-bicarbonate (4.5% albumin). After 20 min during which antagonist drugs were present, the lungs were either hyperventilated or agonist drugs were added. After another 15 min lungs were lavaged. Peak inspired pressures (PIP) in excess of 12 cmH2O produced progressively greater phospholipid (PL) yields. Whereas ventilating with PIP of 9 cmH2O and end-expire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(34 citation statements)
references
References 0 publications
2
32
0
Order By: Relevance
“…Wyszogrodski et al (55) found that increased ventilation in experimental animal models led to an increased usage of surfactant. Spontaneously breathing rabbits had an increased amount of phospholipid in bronchoalveolar lavages following hyperventilation (34); further in vitro and in vivo studies confirmed that hyperventilation through mechanical distension induces surfactant release (30,53,54). The presence of pulmonary surfactant in excess may be particularly important for seals, which repeatedly dive to forage.…”
Section: Discussionmentioning
confidence: 98%
“…Wyszogrodski et al (55) found that increased ventilation in experimental animal models led to an increased usage of surfactant. Spontaneously breathing rabbits had an increased amount of phospholipid in bronchoalveolar lavages following hyperventilation (34); further in vitro and in vivo studies confirmed that hyperventilation through mechanical distension induces surfactant release (30,53,54). The presence of pulmonary surfactant in excess may be particularly important for seals, which repeatedly dive to forage.…”
Section: Discussionmentioning
confidence: 98%
“…There is extensive experimental evidence to indicate that lung inflation increases the production of surfactant phospholipids in intact animals (7,21,40), isolated organs (7,18,19), and by cells in culture (6,38). For example, Wirtz and Dobbs (38) showed the effect of a single mechanical stretch on TII cell surfactant phospholipid secretion, although surprisingly, the effect was not sustained by subsequent stretches.…”
Section: Discussionmentioning
confidence: 99%
“…A large inflation or sigh, deaggregates the surfactant that is sedimented at low centrifugal forces thereby increasing the pool of more rapidly adsorbing surfactant (5, 6), which in turn increases the rate at which losses from the surface film may be replaced by surfactant in the hypophase, thereby restoring alveolar stability. This explanation for the corrective action of a large breath does not preclude a contribution of surfactant, newly secreted in response to a large inflation (19)(20)(21)(22)(23)(24), to the improved alveolar stability. However, the amount of surfactant secreted in response to a single large inflation (23) is substantially less than that generated by deaggregation of easily pelleted material (5,6).…”
mentioning
confidence: 98%